Environmental stratification and optimization of a multi-environment trial net for soybean genotypes in Cerrado - Branquinho, Rodrigo Gomes; Duarte, João Batista; Souza, Plínio Itamar Mello de; Silva Neto, Sebastião Pedro da; Pacheco, Roberto Miranda (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to establish a consistent environmental stratification for recommendation and evaluation of experimental soybean lines and cultivars in the Cerrado region, from the analyses of genotype by environment interaction (GxE) for grain yield, besides evaluating the current trial network on the value for cultivation and use (VCU), for its optimization. Data were obtained from 559 competition trials of soybean lines, performed in 57 locations, during seven harvest periods (2002/2003 to 2008/2009). Joint analyses of variance were carried out by the AMMI (additive main effects and multiplicative interaction) model, and the environmental stratification by the related statistical approach of “winning genotypes”. The GxE interaction was always significant as a result of the genotype differential response to environmental change. Test locations clustered differently according to maturity groups. Redundancy was observed in 20% of the locations, which indicates the possibility of optimizing the trial network by the elimination or replacement of these locations. The target region should receive different stratifications, congenerous to each maturity group, and may be divided into 22 (early cycle), 23 (medium cycle), and 21 (long cycle) environmental strata.